EFEKTIVITAS METODE BLENDED LEARNING DALAM MENINGKATKAN KEMAMPUAN SISWA DALAM MENGUASAI MATERI SENI BUDAYA NUSANTARA KELAS X TKJ 1 SMK NEGERI 1 DENPASAR - Ni Made Pira Erawati; Gusti Ayu Made Puspawati; I Gede Gusman Adhi Gunawan (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
This study aims to determine the effectiveness of the Blended Learning method in improving students’ ability to master the material on analyzing works of Nusantara art and culture in class X TKJ 1 at SMK Negeri 1 Denpasar. It also aims to describe how the implementation of Blended Learning affects student motivation and engagement in learning. Blended Learning is an instructional approach that combines face-to-face learning with online learning, offering flexibility, interactivity, and a student-centered learning environment. This research is a Classroom Action Research (CAR) conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection stages. The research subjects were 32 students from class X TKJ 1 SMK Negeri 1 Denpasar in the 2024/2025 academic year. Data collection techniques included learning achievement tests, student response questionnaires, and observation sheets. The results showed that the implementation of the Blended Learning method effectively improved student learning outcomes. The average score increased from 64.78 in the pre-cycle to 73.28 in cycle I, and reached 83.53 in cycle II. Additionally, students' learning responses improved significantly, as indicated by increased observation scores and positive questionnaire results in each cycle. These findings confirm that Blended Learning is effective in enhancing both the cognitive abilities and affective engagement of students in the subject of Art and Culture. Therefore, Blended Learning can be considered an effective alternative strategy for improving the quality of Art and Culture education, particularly in the context of 21st-century learning that demands the integration of technology and adaptive approaches.